Bisphenol A, the Villain of Plastics: Chemistry Teaching to Raise Students’ Awareness in a High School in Southeastern Brazil - Carrijo, Victor de Sousa; de Souza, João Iamin F. Rebouças; Miranda, Mayker Lazaro Dantas (Orbital: The Electronic Journal of Chemistry, 2020)
Traditional expository classes, whose only didactic resources are the blackboard and the teacher’s talk, are neither the only alternative nor the most productive one to teach Chemistry. Keeping it in mind, this study aimed at addressing one of several topics in Chemistry – plastics – by problematizing everyday situations, since the composition of some plastic packaging includes harmful compounds, such as bisphenol A (BPA). Specifically, BPA is an industrial chemical product which has been broadly used in its monomeric form to yield epoxy resins and polycarbonate plastics. Since it has excellent physical and chemical characteristics, it has been used as lining of metal packaging, besides the manufacturing of milk bottles and household items. However, BPA, even at low concentrations, may cause infertility, nervous system disorders, diabetes, cancer, obesity, precocious puberty and cardiovascular diseases. In order to make Chemistry teaching more attractive, this study aimed at informing students about effects of BPA at the Instituto Federal do Triângulo Mineiro - Campus Uberlândia Centro (IFTM - UDICENTRO), a high school located in Uberlândia, Minas Gerais (MG) state, Brazil. Thus, questionnaire about BPA was applied to the students and the theme and the adverse effects of this compound were discussed from a chemical point of view. Results of the study and both students’ learning and awareness-raising were considered satisfactory. Teaching which includes students’ reality is capable of improving their comprehension and make Chemistry classes more attractive and pleasant. DOI: http://dx.doi.org/10.17807/orbital.v12i2.1448